Photoelectrodes: Vertically Aligned Ta3N5 Nanorod Arrays for Solar‐Driven Photoelectrochemical Water Splitting (Adv. Mater. 1/2013). (2nd January 2013) - Li, Yanbo; Takata, Tsuyoshi; Cha, Dongkyu; Takanabe, Kazuhiro; Minegishi, Tsutomu; Kubota, Jun; Domen, Kazunari
<x xml:space="preserve">Abstract</x> A highly efficient nanorod photoanode for solar‐driven photoelectrochemical (PEC) water splitting is reported by Kazunari Domen and co‐workers on page 125. The cover image illustrates vertically aligned semiconductor nanorods grown in situ on a metal substrate. The single crystalline 1D nanostructure with low contact barrier makes them ideal building blocks of PEC cells for efficient solar energy conversion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>